IMPLEMENTASI METODE QUALITY CONTROL CIRCLE UNTUK PENINGKATAN KAPASITAS PRODUKSI PROPELLER SHAFT DI PT XYZ - Ahmad Yunus Nasution; Sulis Yulianto (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2018)
PT.XYZ is a company manufacture automotive under body parts. With the policy of adding new models, so that the loading line propeller shaft 2 joint will increase, where in the production line is not sufficient with high loading production so that the production capacity is not adequate. In order for production capacity can be achieved according to target, needed improvement. In this discussion, the improvement will be related to the process of assy propeller shaft 2 joint. The method used in this research is QCC (Quality Control Circle). This method is appointed by the author for supporting the program of countinous improvement in the company. Sub assy process is a process with the highest cycle time, so the production capacity of the line propeller shaft 2 joint is not sufficient. After the observation with the QCC method of work elements sub assy process is the highest handling replacement fixture. The focal point of the improvement that will be done now is the fixture modification of the sub assy process. After improving the working elements of the handling fixture, the cycle time sub assy process decreased from 85 seconds to 70 seconds and the production line of line propeller shaft 2 joint increased from 96% to 100%.